Fibroblast Growth Factor (FGF-2) and Its Receptors FGFR-2 and FGFR-3 May Be Putative Biomarkers of Malignant Transformation of Potentially Malignant Oral Lesions into Oral Squamous Cell Carcinoma - Nayak, Seema; Goel, Madhu Mati; Makker, Annu; Bhatia, Vikram; Chandra, Saumya; Kumar, Sandeep; Agarwal, S. P. (PLOS ONE, 2015)
There are several factors like angiogenesis, lymphangiogenesis, genetic alterations, mutational factors that are involved in malignant transformation of potentially malignant oral lesions (PMOLs) to oral squamous cell carcinoma (OSCC). Fibroblast growth factor-2 (FGF-2) is one of the prototypes of the large family of growth factors that bind heparin. FGF-2 induces angiogenesis and its receptors may play a role in synthesis of collagen. FGFs are involved in transmission of signals between the epithelium and connective tissue, and influence growth and differentiation of a wide variety of tissue including epithelia. The present study was undertaken to analyze expression of FGF-2 and its receptors FGFR-2 and FGFR-3 in 72 PMOLs, 108 OSCC and 52 healthy controls, and their role in risk assessment for malignant transformation of Leukoplakia (LKP) and Oral submucous fibrosis (OSMF) to OSCC. Immunohistochemistry was performed using antibodies against FGF-2, FGFR-2 and FGFR-3. IHC results were validated by Real Time PCR. Expression of FGF-2, FGFR-2 and FGFR-3 was upregulated from PMOLs to OSCC. While 90% (9/10) of PMOLs which showed malignant transformation (transformed) expressed FGF-2, only 24.19% cases (15/62) of PMOLs which were not transformed (untransformed) to OSCC expressed FGF-2. Similarly, FGFR-2 expression was seen in 16/62 (25.81%) of untransformed PMOLs and 8/10 (80%) cases of transformed PMOLs. FGFR-3 expression was observed in 23/62 (37.10%) cases of untransformed PMOLs and 6/10 (60%) cases of transformed PMOLs. A significant association of FGF-2 and FGFR-2 expression with malignant transformation from PMOLs to OSCC was observed both at phenotypic and molecular level. The results suggest that FGF-2 and FGFR-2 may be useful as biomarkers of malignant transformation in patients with OSMF and LKP.